Comparison of perinatal outcomes of selective termination in dichorionic twin pregnancies performed at different gestational ages. (18th June 2017) - Dural, Ozlem; Yasa, Cenk; Kalelioglu, Ibrahim H.; Can, Sultan; Yılmaz, Gamze; Corbacioglu Esmer, Aytul; Has, Recep; Yuksel, Atil
Abstract: Objective : To determine the perinatal outcomes of selective termination in dichorionic twin pregnancies discordant for major but non-lethal fetal anomalies performed at different gestational ages. Methods : Thirty-one dichorionic twin pregnancies that underwent selective termination for discordant major but non-lethal fetal anomalies between January 2004 and February 2015 were retrospectively reviewed. The patients were grouped into three, according to the gestational age at which selective termination of pregnancies was performed; Group 1 (15–19 weeks), Group 2 (20–24 weeks) and Group 3 (30–33 weeks). Perinatal outcomes in all the three groups were reviewed and analyzed. Results : The overall live birth, term birth and pregnancy loss rate were 93.6%, 54.8% and 9.6%, respectively. The overall live birth rate was 66.6% in Group 1, this rate was 100% in Group 2 and Group 3 ( p = 0.01). The rate of pregnancy loss was significantly higher in Group 1 ( p = 0.01). The overall preterm delivery rate was 38.7%. While the overall preterm delivery rate was significantly higher in Group 3 ( p = 0.04), the rate of extremely and very preterm birth was significantly lower ( p = 0.03). Conclusion : Late selective feticide performed during the third trimester of pregnancy seems to be a safe approach and can be offered as an alternative method to reduce the total pregnancy loss and extremely and early pre-term birth rates.